PENGARUH EARNINGS PER SHARE (EPS), RETURN ON EQUITY (ROE), DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM MELALUI NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2020-2024. - Rahman Fauzi Akbar; Nanu Hasanuh; Solihin Sidik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Equity (ROE), and Debt to Equity Ratio (DER) on stock returns, with Price to Book Value (PBV) as an intervening variable in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study uses a quantitative approach with a causal associative design and hypothesis testing using path analysis techniques. The study population includes all banking companies listed on the IDX, with 20 companies selected as samples through a purposive sampling method, resulting in a total of 100 observational analysis units. Data analysis was performed using panel data regression, with the Fixed Effect Model (FEM) selected as the best estimation model. Partial test results indicate that ROE has a positive and significant effect on firm value, while EPS and DER have no significant effect. Direct testing of stock returns found that only DER has a positive and significant effect, while EPS, ROE, and firm value do not have a significant direct effect. Furthermore, the Sobel test results confirm that firm value is unable to act significantly as an intervening variable in mediating the effects of EPS, ROE, or DER on stock returns. The conclusion of this study indicates that the transmission mechanism of financial fundamentals to stock returns in the banking sector is not realized through the appreciation of the company's book value.